2022
DOI: 10.1097/scs.0000000000008646
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Skeletal Maturation in Male Children With Unilateral Cleft Lip and Palate

Abstract: Objectives: To assess the skeletal maturation in male children with unilateral cleft lip and palate (UCLP) in comparison to that of noncleft peers using the cervical vertebral maturation (CVM) method. Methods: A sample of 149 male UCLP patients aged from 8- to 16-year-old and 447 age-matched orthodontic individuals without clefts was retrospectively compiled. Cervical vertebral maturation was assessed based on the cephalometric radiographs. Results: The proportion of children in CVMSI and CVMSII was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…27 Previous literature also reported that cleft boys delay in attaining skeletal maturation than non-cleft boys. 25,28,40 These data support the need for keeping both sex and diagnostic categories separate when conducting etiological searches. In addition, cleft children might show slight growth retardation in early maturational stages, but they catch up with normal growth during the pubertal growth spurt.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…27 Previous literature also reported that cleft boys delay in attaining skeletal maturation than non-cleft boys. 25,28,40 These data support the need for keeping both sex and diagnostic categories separate when conducting etiological searches. In addition, cleft children might show slight growth retardation in early maturational stages, but they catch up with normal growth during the pubertal growth spurt.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, another study reported a delay in skeletal maturation before the pubertal growth spurt of (pre)adolescents with CL/P, especially girls 27 . Previous literature also reported that cleft boys delay in attaining skeletal maturation than non-cleft boys 25,28,40 . These data support the need for keeping both sex and diagnostic categories separate when conducting etiological searches.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, congenital cervical vertebrae anomalies have been reported in patients with CL/P [14], thus indicating that skeletal maturation is affected by the disease. Our previous research found that when boys with unilateral complete cleft lip and palate (UCLP) were 12 to 14 years-of-age, their skeletal maturity was significantly delayed when compared to controls [15]. However, there is no general agreement on whether CL/P patients and normal controls have different levels of skeletal maturity [16].…”
Section: Introductionmentioning
confidence: 99%